Polymerase chain reaction and restriction fragment length polymorphism of cytocrome oxidase subunit I used for differentiation of Brazilian Biomphalaria species intermediate host of Schistosoma mansoni - Teofânia HDA Vidigal; Lângia C Montresor; Andrew JG Simpson; Omar S Carvalho (Memorias do Instituto Oswaldo Cruz, 2002)
The intermediate hosts of Schistosoma mansoni, in Brazil, Biomphalaria glabrata, B. tenagophila and B. straminea, were identified by restriction fragment length polymorphism analysis of the mitochondrial gene cytochrome oxidase I (COI). We performed digestions with two enzymes (AluI and RsaI), previously selected, based on sequences available in Genbank. The profiles obtained with RsaI showed to be the most informative once they were polymorphic patterns, corroborating with much morphological data. In addition, we performed COI digestion of B. straminea snails from Uruguay and Argentina.